Municipal Projects Supporting the Education and Training of Adults from Vulnerable Groups - Mirela Kyuchukova (Педагогически форум, 2025)
The article defines the role of municipal projects in supporting the education and training of adults from vulnerable groups, including the Roma community. Through National Programmes, European policies provide funding that encourages Bulgarian municipalities to develop project-based initiatives aimed at addressing issues relevant to their local communities. Projects focused on adult education for individuals from vulnerable backgrounds offer a variety of learning opportunities—ranging from motivational and vocational training to courses designed to develop personal qualities and skills. These initiatives also support the use of mediation practices by employing health, education, labour, and youth mediators. These professionals play a key role in building connections with adults from vulnerable groups and helping them overcome barriers to learning and engagement in the educational systems. The emphasis on identifying and researching local challenges within municipal project work enables the creation of successful inter-institutional partnerships, which in turn strengthen the resources and capacity of local institutions.